Yield and economics of clusterbean as influenced by different weed control measures - Singh, S.P.; Yadav, R.S.; Kumawat, Amit; Jakhar, R.R. (Annals of Agricultural Research, 2019)
To test the efficacy of different weed control measures against weeds in clusterbean a field experiment was conducted at Research Farm of SKRAU, Bikaner during Kharif seasons of 2013 and 2014 comprising seven weed control treatments consisting of imazethapyr 40g/ha, quizalofop ethyl 37.5 g/ha, fenoxaprop-p-ethyl 50g/ha, imazethapyr + imazamox 40g/ha, pendimethalin 0.75kg/ha (PE), hand weeding twice at 20 and 40 DAS and weedy check in randomized block design (RBD) with four replications. Among herbicidal treatments, post -emergence application of imazethapyr + imazamox (ready mix) 40 g/ha applied at 3-4 leaf stage (20 DAS) recorded lowest weed density and dry weight of both grassy and broad leaved weeds. Application of imazethapyr alone at 40 g/ha applied at 3-4 leaf stage (around 20 DAS) significantly reduced the density and dry weight of broad leaved weeds but not effective significantly against grassy weeds. Plant height, pods/plant, seed and straw yields, net return and B:C ratio was also superior with imazethapyr + imazamox 40 g/ha applied at 3-4 leaf stage.